Safety, tolerability and immunogenicity of an active anti‐Aβ40 vaccine (ABvac40) in patients with amnestic mild cognitive impairment (A‐MCI) or very mild alzheimer's disease (VM‐AD): A randomized, double‐blind, placebo‐controlled, phase II trial: Human/Human trials: Anti‐amyloid. (7th December 2020) - Molina, Elisabet P.; Pesini, Pedro; Sarasa‐SanJose, Manuel; Marcos, Ivan; Lacosta, Ana M.; Allué, Jose A.; Fandos, Noelia; Sarasa, Manuel; Boada, Mercè; ,
Abstract: Background: Alzheimer's disease is one of the biggest burdens of society with a dramatic and growing worldwide incidence rate. Notwithstanding scientific and medical advances, the condition remains incurable. Immunotherapies intended to act on the amyloid cascade are currently among the most hopefully disease modifying approaches Αβ40 is in the core of the amyloid plaques and is the main component of vascular amyloid deposition which is associated with earlier dementia onset in AD. These data leads further the hypothesis that it should be targeted in treatment strategies. Araclon Biotech is developing an active vaccine directed specifically against the Aβ‐40 peptide. Method: This is a phase II, double‐blind, randomized, placebo‐ controlled study in patients with amnestic mild cognitive impairment (a‐MCI) or very mild Alzheimer's Disease (Vm‐AD). The study will last for 104 weeks (from V0 to V25) during which the patients will receive five monthly (every four weeks) immunizations plus a booster shot. The primary objective of this trial is to confirm the safety, tolerability and biological activity (immunogenicity) results obtained in phase I and to explore the effect of the treatment on disease biomarkers (neuroimaging, CSF and plasma) and cognition as secondary efficacy variables. Result: Recruitment has been completed. 124 patients aged 55 to 80 have been included in the study (a‐MCI, n= 80; Vm‐AD, n= 44). Baseline demographics and characteristics were balanced. To date, fifty patients have completed the first year study (treatment period). Conclusion: Interim findings to be presented at the congress.